Is the provision of rehabilitation in adult hearing services warranted? A cost benefit analysis. Issue 25 (4th December 2021) - Hogan, Anthony; Donnelly, David; Ferguson, Melanie; Boisvert, Isabelle; Wu, Eric
Abstract: Purpose: To examine the extent to which there is a basic economic case for the provision of rehabilitation services within a publicly funded, device-centred approach to adult hearing services. Materials and methods: Five representative cross-sectional surveys of people aged 50 years and over were conducted in Australia between 2013 and 2019 ( n = 4663). Respondents were surveyed on self-rated hearing abilities, hearing aid usage and perceived benefits of device usage. A population estimate of non-device usage was derived from these data and the costs and benefits of the existing versus proposed hearing services pathways examined. Results: Among respondents 27% reported that their hearing was fair or poor, and 14% reported hearing aid ownership. 45% of hearing aid owners were regular device users. Approximately 1:4 people (24%) who owned a hearing aid had not used it in the past three months; with an estimated cost of au87.4 million per annum. The provision of hearing rehabilitation services in addition to or instead of hearing aids could provide clients with a more comprehensive service at an estimated saving of between 62% to 81% of existing program costs. Conclusions: Cost benefit analysis supports the provision of hearing rehabilitation within a hearing services program, either as an alternative to the existing service, or adjunct to it. Such a service would enhance client outcomes and reduce the level of wastage currently associated with the current device-centred approach. Implications for rehabilitation: Clients identified as not being immediately ready to progress to hearing aids could benefit from rehabilitation programs while still having access to either assistive listening devices or hearing aids. The proposed approach could result in significant cost savings to publicly funded programs while ensuring better outcomes for service users through the more effective, efficient and ethical use of public monies.